Errores comunes sobre relatividad entre los profesores de enseñanza secundaria - Alemany Berenguer, Rafael Andrés (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
The limited understanding of the Principle of Relativity and its vague and ambiguous formulation in most text-books, may be some of the sources of very common misconceptions on explaining this outstanding piece of the 20th century science. To diagnose these misconceptions a general check of many of books was carried out with the results that are expounded in this work. The conclusions revealed that mistakes emerged through misunderstanding of modern physics assumptions about the proper nature of reality, and difficulty in transfehng those new ideas to operative thought in order to achieve an effective learning.